Om att inspireras och om att åstadkomma en kreativ forskningsmiljö - Klein, Barbro (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2011)
This essay concerns the meeting between Billy Ehn and Barbro Klein in 1984 at the Institute for Folklife Research in Stockholm to which both had returned after long absences. The text describes how we inspired each other as scholars and teachers and how we arranged the seminars on reflexivity that eventually led to ‘From experience to text’. This book came to have an unforeseen impact. A conclusion is that the unexpected constellation of energies and scholarly concerns helped shaping an open and inviting research atmosphere. This underscores the importance of serendipitous meetings between scholars with different experiences.